2023
DOI: 10.1002/smll.202307585
|View full text |Cite
|
Sign up to set email alerts
|

High‐Affinity Host–Guest Recognition for Efficient Assembly and Enzymatic Responsiveness of DNA Nanostructures

Raghu Pradeep Narayanan,
Abhay Prasad,
Alex Buchberger
et al.

Abstract: The combination of multiple orthogonal interactions enables hierarchical complexity in self‐assembled nanoscale materials. Here, efficient supramolecular polymerization of DNA origami nanostructures is demonstrated using a multivalent display of small molecule host–guest interactions. Modification of DNA strands with cucurbit[7]uril (CB[7]) and its adamantane guest, yielding a supramolecular complex with an affinity of order 1010 m−1, directs hierarchical assembly of origami monomers into 1D nanofibers. This a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…In addition, high-affinity ADA/CB[n] interaction between functionalized DNA strands could direct hierarchical assembly of origami monomers into DNA nanofibers of micrometer-length. 294 As another fascinating example of bioapplicable nanomaterial important for understanding and diagnosing The supramolecular system was constructed with ADA and CB [7] functionalized with luminol and AIEgen, respectively, using the resulting host-guest interactions to produce efficient bioluminescence resonance energy transfer (BRET) from blue-emissive luminol to red-emissive AIEgen, thus providing fluorescent imaging. 266 In the end, we will present one recent example of AuNPs combined with a different host-guest ADA/CB[n] supramolecular system that was developed for quantitative detection of SARS-CoV-2 antibodies in human serum.…”
Section: Interdisciplinary Applications and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, high-affinity ADA/CB[n] interaction between functionalized DNA strands could direct hierarchical assembly of origami monomers into DNA nanofibers of micrometer-length. 294 As another fascinating example of bioapplicable nanomaterial important for understanding and diagnosing The supramolecular system was constructed with ADA and CB [7] functionalized with luminol and AIEgen, respectively, using the resulting host-guest interactions to produce efficient bioluminescence resonance energy transfer (BRET) from blue-emissive luminol to red-emissive AIEgen, thus providing fluorescent imaging. 266 In the end, we will present one recent example of AuNPs combined with a different host-guest ADA/CB[n] supramolecular system that was developed for quantitative detection of SARS-CoV-2 antibodies in human serum.…”
Section: Interdisciplinary Applications and Perspectivesmentioning
confidence: 99%
“…In addition, high-affinity ADA/CB[ n ] interaction between functionalized DNA strands could direct hierarchical assembly of origami monomers into DNA nanofibers of micrometer-length. 294 …”
Section: Cucurbit[ N ]Urils In Drug Deliverymentioning
confidence: 99%
“…At the turn of 2023, a series of preliminary reports demonstrated that gene-encoded synthetic deoxyribonucleic acid (DNA) nanoparticles (NPs) can enable protein expression via transcription and translation in vitro and in vivo. Simultaneously, custom DNA origami NPs with multiple enzymatically encoded functional modifications are gaining traction for biomedical applications. In these rapidly growing nanoscale applications of synthetic DNA origami NPs, the role of the scaffold strandwhich is the long single-stranded template DNA (ssDNA) within these particleshas become multifaceted. The traditional DNA origami NPsmade predominantly with scaffolds sourced from bacteriophage’s canonical genomic ssDNAsare still widely applied in single molecular studies, photonics, plasmonic, and biomedical applications, but a new suite of DNA NPs leverage nonviral sequences as scaffold strands to serve functional roles. , These scaffold strands are produced by enzymes (such as asymmetric polymerase chain reaction (aPCR)) by separating ssDNA from double-stranded DNA (dsDNA) or phage-based methods, often requiring purification .…”
Section: Introductionmentioning
confidence: 99%